AKTIVITAS BELAJAR DAN STRUKTUR BELAJAR PADA ANAK AUTIS DI SEKOLAH LUAR BIASA YAYASAN HARAPAN BUNDA DUMAI (YHBD) KOTA DUMAI - Yasnawati, Rika; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Autism is a brain disorder that affects the person's development. Autism is a pervasive developmental disorder in children characterized by the disruption and delays in cognitive, language, behavior, communication and social integration. This study aims to determine the learning activities and learning structures of autistic children in Yayasan Harapan Bunda Dumai, to learn the knowledge and skills of teachers in the learning process of children with autism in Yayasan Harapan Bunda Dumai and to identify perceived barriers when teachers give lessons to children with autism in the Foundation Harapan Bunda Dumai. The theory used in this research that socialization theory and the theory of the role. Socialization is a learning process experienced by a person to gain knowledge about the values and norms so that he could participate as a member of a group in society. Role is as a set of expectations imposed on individuals who occupy a particular social position.Keywords: Autism, Activities, Knowledge, Socialization, Role